Nutritional composition and cost differences between gluten-free and gluten-containing food products in Kuala Lumpur, Malaysia - Mohd Fauad, Siti Nur Aishah; Kaur, Satvinder; Shafie, Siti Raihanah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: The demand for commercial gluten-free food products are increasing due to rising prevalence of lifestyle-related diseases. The market growth is forecasted to increase in numbers. However, to date nutritional comparison of gluten-free and gluten-containing food products is not done extensively in Malaysia. Therefore, this study aimed to investigate the nutritional composition and cost per 100 g between gluten-free and gluten-containing food products in selected grocery stores in Kuala Lumpur. Methods: A total of 106 food products comprising of gluten-free food products (n=41) and gluten-containing food products (n=65) were determined and compared for its nutritional composition and cost per 100 g. The products were obtained from 4 main grocery stores in Kuala Lumpur that supply gluten-free food products. The differences in nutritional composition and cost between both products were analysed by using independent samples t-test. Results: The results showed no difference in energy content between both products. Across the food products, 15 % of gluten-free food products showed higher carbohydrate content compared to its counterparts. Protein content in gluten-free products was 63 % lower than gluten-containing products. Among all gluten-free food products included in this study, only lasagne sheet has lower content of dietary fibre compared to its counterparts. The cost for majority of gluten-free food products was significantly higher, which was two- to fourfold higher compared to gluten-containing products. Conclusion: This study indicated that gluten-free food products showed no nutritional advantage especially in its macronutrients, hence, avoidance of gluten for healthy population may not be beneficial and rather costly.